Benign Breast Changes with Adenosis and Duct Ectasia: Diagnostic Challenges and Clinical Implications - Saeed, Nur; Chaudhary, Zayn (Biological and Clinical Sciences Research Journal, 2025)
Rapidly enlarging breast masses during pregnancy pose significant diagnostic challenges. Physiologic breast changes can mask or mimic underlying pathology, and limited biopsy samples may reveal only benign elements such as adenosis, duct ectasia, or tubular adenoma despite an underlying fibroepithelial lesion. Case Presentation: A 34-year-old pregnant woman in her second to third trimester presented with a 1.5-year history of a progressively enlarging left breast mass that rapidly increased in size and became fungating during pregnancy. Earlier histopathology revealed adenosis and duct ectasia, while fine-needle aspiration cytology (FNAC) was reported as C3 ("atypical, probably benign"). Ultrasonography demonstrated an approximately 11 cm multilobulated, hypervascular, exophytic mass classified as BI-RADS 4 B. A wedge biopsy during pregnancy showed a tubular adenoma. Given the lesion's aggressive growth and clinicoradiologic–pathologic discordance, a total left mastectomy was performed. Final histopathology confirmed a benign phyllodes tumour with skin ulceration and a deep margin of 1 mm. Intervention and Outcome: The patient underwent a total mastectomy with complete tumour removal and no perioperative complications. Considering the close deep margin, structured postoperative surveillance was advised. Conclusion: In pregnancy, rapidly growing breast masses with benign or indeterminate histology warrant escalation to complete excision, especially when clinical, radiologic, and histopathologic findings are discordant. This case underscores diagnostic overlap among adenosis, duct ectasia, tubular adenoma, fibroadenoma, and phyllodes tumour and highlights the importance of margin-oriented surgery and long-term follow-up.